Decision Making in Financial Behavior: A Systematic Literature Review¬ - Havidotinnisa, Siti; Puspasari, Dewi; Purnomo , Budi Supriatono; Purnamasari, Imas (West Science Social and Humanities Studies, 2024)
Digitalization is a major factor in the rapid dissemination of information, especially in the financial world. This has an impact on the emergence of various financial behaviors that can affect Investor Decision Making in investing. Financial behavior is a key factor that can affect the quality of Investor Decision Making, which is characterized by achieving optimal results and avoiding biased decisions. Effective financial behaviors are very important and should not be taken lightly. As an investor, adopting appropriate financial behaviors is key to overcoming behavioral biases associated with Investor Decision Making. The purpose of this study is to investigate the current state of behavioral finance research with a focus on the significant factors that influence Investor Decision Making. Driven by the need to create a comprehensive literature on peer pressure, this study used a bibliometric approach by identifying 92 studies using the term "behavioral finance" from the Scopus database. The most frequently reviewed articles were analyzed to highlight key contributions and provide general information about the field. All mentioned information covers several aspects, such as the relationship between investors, fund managers, the investment industry, and the significant influence of behavioral finance on Investor Decision Making. The practical implications of this study have the potential to be a valuable reference for researchers and practitioners, assisting in the development of clear and concise conclusions with relevant context. Investors should be encouraged to integrate their internal processes with the results of bibliometric analysis. This research emphasizes the importance of behavioral finance in Investor Decision Making, provides insight into the current state of research, and the role of researchers in developing a critical understanding of Investor Decision Making.